Methods of Teaching English in Secondary Schools: A Scientific Exploration of Approaches - Berdimurodova Marhabo (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This scientific article examines various methods employed in teaching English in secondary schools, considering their theoretical foundations, effectiveness, and challenges. With English becoming a global lingua franca, it is crucial to adopt diverse pedagogical strategies to accommodate the needs of learners. By investigating established teaching methods—such as the Grammar-Translation Method, Direct Method, Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), and Audiolingual Method—this study aims to provide insights into the best practices for fostering English language acquisition in secondary education. The paper analyzes each method, reviews empirical research, and proposes recommendations for teachers.